The status of the academic library profession in Isabela an assessment - Enriquez, Zoilo Canceran; Faderon, Rosalie B.; Santos, Herminia H. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2005)
Academic librarians of today have a significant role and are considered special agents of colleges and universities in contributing towards the realization of the institutional mission and vision. The librarians are actively involved in the formulation and implementation of the colleges' and universities' goals and objectives. Thus, the academic library profession in Isabela deserves recognition from the public.
This study primarily assessed the status of academic librarianship in Isabela as of school year 2004-2005, as to the profile, problems and extent of administrative support to the academic librarians in colleges and universities in Isabela.
The twenty four (24) librarians in fifteen(15) colleges and universities in Isabela comprised the respondents of this study.
The descriptive method of research was used. The research instruments were a structured questionnaire and an interview schedule. This study also utilized the standards set by the Philippine Association of Academic and Research Libraries (PAARL) in assessing the status of the academic librarians in Isabela.
In general, the academic institutions in Isabela have minimally complied with the PAARL standards for librarians.
Vita.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Academic librarians -- Philippines -- Isabela; Academic libraries -- Evaluation. -- Philippines -- Isabela